Beyond Glycemia: Independent Hemodynamic and Metabolic Drivers of Incident Diabetic Kidney Disease in a 5-Year Prospective Indonesian Primary Care Cohort - Juliana; Nelly (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The relative contributions of hyperglycemia, hypertension, and metabolic adiposity to the progression of diabetic kidney disease (DKD) are debated, particularly in Southeast Asian populations and in the context of modern polypharmacy. We aimed to prospectively quantify the independent impact of glycemic burden, hemodynamic stress, and central adiposity on the 5-year incidence of DKD in an Indonesian primary care cohort. Methods: We conducted a 5-year, multi-center, prospective cohort study at 25 primary care clinics in Indonesia. We randomly sampled and enrolled 1,250 T2DM patients without pre-existing DKD (eGFR > 60 mL/min/1.73m² and normoalbuminuria). The primary composite outcome was incident DKD, defined as persistent albuminuria (ACR ≥ 30 mg/g on 2 of 3 occasions) or a sustained eGFR decline of ≥ 30%. Baseline predictors included HbA1c, Systolic Blood Pressure (SBP), and Waist-to-Height Ratio (WHtR). Multivariable Cox proportional-hazards models were used to estimate Hazard Ratios (HRs), adjusting for demographics, baseline eGFR, and baseline use of RAAS inhibitors (RAASi) and SGLT2 inhibitors. Results: Of 1,250 participants, 980 (78.4%) completed the 5-year follow-up. Over a median 4.9 years, 215 participants (21.9%) developed the composite DKD outcome. In the fully-adjusted multivariable Cox model, all three pathways were strong, independent predictors of incident DKD. The standardized HR for SBP (per 1-SD increase) was 1.68 (95% CI: 1.40–2.01; p<0.001), for HbA1c (per 1-SD increase) was 1.45 (95% CI: 1.22–1.73; p<0.001), and for WHtR (per 1-SD increase) was 1.39 (95% CI: 1.18–1.65; p<0.001). Conclusion: In this prospective primary care cohort, hemodynamic stress (SBP), glycemic burden (HbA1c), and metabolic adiposity (WHtR) were all independent, potent drivers of incident DKD, even after controlling for the use of protective cardio-renal medications. These findings confirm that a multi-pillar strategy, aggressively targeting blood pressure, glucose, and weight/metabolic health simultaneously, is essential for DKD prevention.